• عربي

Need Help?

Subscribe to Calculus B

###### \${selected_topic_name}
• Notes

Evaluate $\int \frac{\cos (x)}{7+5 \sin (x)-\cos ^{2}(x)} d x$

$u=\sin (x) \longrightarrow d u=\cos (x) d x$

$\cos ^{2}(x)=\left(1-\sin ^{2}(x)\right)$

$\cos ^{2} x+\sin ^{2} x=1$

$I=\int \frac{\cos (x)}{7+5 \sin (x)-\left(1-\sin ^{2}(x)\right)}=\int \frac{d u}{7+5 u-\left(1-u^{2}\right)}$

$=\int \frac {d u}{7+5 u -1+u^{2}}=\int \frac{d u}{u^{2}+5 u+6}$

$I=\int \frac{d u}{u^{2}+5 u+6}=\int \frac{d u}{(u+2)(u+3)}=\int \frac{A}{u+2} d u+\int \frac{B}{u+3} d u$

$A=(u+2) \cdot\left.fu \right|_{u=-2}=(u+2) \cdot\left.\frac{1}{(u+2)(u+3)}\right|_{u=-2}=\left.\frac{1}{u+3}\right|_{u=-2}=1$

$B=(u+3) f\left.(u)\right|_{u=-3}=(u+3) \cdot\left.\frac{1}{(u+2) (u+3)}\right|_{u=-3}=-1$

$I=\int \frac{du}{u^{2}+{5u}+6}=\int \frac{1}{u+2} d u+\int \frac{-1}{u+3} d u$

$=\ln |u+2|-\ln |u+3|+c$

$\int \frac{\cos (x)}{7+5 \sin (x)-\cos ^{2}(x)} d x=\ln |\sin (x)+2|-\ln |\sin (x)+3|+c$

$\ln a-\ln b=\ln \left|\frac{a}{b}\right|$

$\int \frac{\cos (x)}{7+5 \sin (x)-\cos ^{2}(x)}dx=\ln \left|\frac{\sin (x)+2}{\sin (x)+3}\right|+c$

Evaluate $I=\int \frac{\sqrt{x}}{1+\sqrt[3]{x}} d x$

$\sqrt[2]{x}, \sqrt[3]{x}=6$

let $t^{6}=x \Rightarrow d x=6 t^{5} d t$

$\sqrt{x}=\sqrt{t^{6}}=t^{\frac{6}{2}}=t^{3} \quad \sqrt[3]{x}=\sqrt[3]{t^{6}}=t^{\frac{6}{3}}=t^{2}$

$I=\int \frac{\sqrt{x}}{1+\sqrt[3]{x}} d x=\int \frac{t^{3}}{1+t^{2}}\left(6 t^{5} d t\right)$

$=6 \int \frac{t^{8}}{1+t^{2}} d t$

long division  قسمة مطولة

$I=\int \frac{\sqrt{x}}{1+\sqrt[3]{3 x}} d x=6 \int \frac{t^{8}}{1+t^{2}} d t=6 \int\left(t^{6}-t^{4}+t^{2}+\frac{1}{t^{2}+1}\right) d t$

$\int \frac{1}{x^{2}+1}=\tan ^{-1}(x)$

$I=6\left[\frac{t^{7}}{7}-\frac{t^{5}}{5}+\frac{t^{3}}{3}-t+\tan ^{-1}(t)\right]+c$

$t^{6 / 6}=x^{1 / 6}$

$t=x^{\frac{1}{6}}$

$I=6\left[\frac{{x^{\frac{1}{6}\cdot {7}}}}{7}-\frac{x^{\frac {1}{6}\cdot 5}}{5}+\frac{x^{\frac{1}{6}\cdot 3}}{3}-x^\frac{1}{6}+\tan ^{-1}\left(x^{\frac{1}{6}}\right)+c\right]$

$I=\frac{6}{7} x^{\frac{7}{6}}-\frac{6}{5} x^{\frac{5}{6}}+\frac{6}{3} x^{\frac{1}{2}}-6x^{\frac{1}{6}}+6\tan ^{-1}\left(x^{\frac{1}{6}}\right)+c$